THE INTENSITY WATCHING TELEVISION TO COMMUNICATION OF PARENTS AND SCHOOLD-AGE CHILDREN (studied in the village of Padas district of Dagangan Madiun regency) - Edy Purnomo; . Muarrofah; Agustina Maunaturrohmah (STIKES Insan Cendekia Medika Jombang, 2012)
Television is a media that most attract attention and electronic goods purchased by many people among other mass media. In today's world of mass media, busied cases of children with media especially watching television, being led to the